Antifungal efficacy of chitosan-mediated fenugreek nanocomposite incorporated in tissue conditioner - Mohika Damle; Ponsekar Abraham Anandapandian; B. Eswaran; Swapnaneel Pradhan; Silvin Joe C J; Shreyas Dhumke (Journal of Oral Biology and Craniofacial Research)
Introduction: The rough surface of dentures, coupled with xerostomia and immunosuppression, fosters microbial growth and colonization, with Candida albicans being a primary culprit. Tissue conditioners, used to reline ill-fitting dentures, can temporarily alleviate discomfort but are prone to microbial colonization. To address this, researchers have explored incorporating antifungal agents directly into tissue conditioners. Nanoparticles, particularly green-synthesized ones derived from fenugreek, have shown significant antifungal efficacy. Combining fenugreek extract with chitosan, can further improve antifungal outcomes due to its excellent drug delivery, mucoadhesive properties, and bioavailability. Aim: To synthesize Chitosan mediated Fenugreek nanocomposite (1.5 %,2 %,2.5 % by weight concentrations) and evaluate its antifungal efficacy on heat cure denture base relined with tissue conditioner mixed with nanocomposite by assessing fungal colony formation after 1st day, 1st week and 2nd week. Methodology: After synthesizing chitosan mediated fenugreek Nanocomposite, its characterization was performed using SEM, FTIR analysis and UV–Vis spectroscopy. Heat cure denture base discs coated with tissue conditioner-nanocomposite mixture were used to transfer fungal cultures onto Rose Bengal agar to assess colony formation. Results and discussion: Chitosan-fenugreek nanoparticles were synthesized using the ionic gelation method, with fenugreek extract used for green synthesis. Kruskal-Wallis test showed significant effects over time, with 2.5 % group showing lowest fungal growth at 521 CFU/mL, followed by 2 % group at 587 CFU/mL, while the 1.5 % nanocomposite group still displayed considerable fungal growth. Conclusion: Incorporating chitosan-mediated fenugreek nanocomposite into denture tissue conditioners offers a promising approach to reducing Candidal growth, potentially improving oral health outcomes for denture wearers.